Analisis Implementasi Keselamatan, Kesehatan, Keamanan, Dan Lingkunngan (K3L) Pada Pelaksanaan Praktik Di Laboratorium SMKN 1 Sukatani Jurusan Teknik Instalasi Tenaga Listrik - Ibrahim, Iman; Dwijaksara, Ni Luh Bella Windu Febriyanti (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research aims to analyze the implementation of Occupational, Health, Security, and Environment (OHSE) in the Electrical Power Installation Department's practical laboratory of Vocational High School 1 Sukatani, Grade 11. The research methodology employed is a quantitative-descriptive approach. The research findings indicate that all students have received counseling related to electrical engineering. The majority of the students, which amounts to 43 individuals (95.6%), are aware of the potential dangers and risks during laboratory practice. However, there are 2 students (4.4%) who have not acquired this knowledge. Regarding the usage of Personal Protective Equipment (PPE), 14 students (31.1%) consistently utilize them, 25 students (55.6%) use them occasionally, and 6 students (13.3%) never use them. Out of the 45 students, 8 have experienced incidents during practice, and 1 out of those 8 did not receive any medical treatment. Furthermore, 14 students (31.1%) always inspect the condition of tools and materials before using them in the laboratory, while the majority of the students occasionally perform these inspections (55.6%), and some never do so (11.1%). Additionally, most students (42.2%) always pay attention to and comply with safety regulations during laboratory practice, but there are some students (6.7%) who never pay attention to or comply with safety regulations.